Human cord blood endothelial progenitors promote post-ischemic angiogenesis in immunocompetent mouse model. Issue 141 (May 2016) - Flex, Andrea; Biscetti, Federico; Iachininoto, Maria Grazia; Nuzzolo, Eugenia Rosa; Orlando, Nicoletta; Capodimonti, Sara; Angelini, Flavia; Valentini, Caterina Giovanna; Bianchi, Maria; Larocca, Luigi Maria; Martini, Maurizio; Teofili, Luciana
Abstract: Background: Human cord blood (CB) endothelial colony forming cells (ECFCs) are endowed with high vascular regenerative ability in immunodeficient mice, but their immunogenicity and susceptibility to rejection in immunocompetent models has yet to be explored. Methods: We injected CB ECFCs in non-immuno-suppressed C57BL/6 J mice after having induced the hindlimb ischemia and we investigated their contribution to the recovery from the ischemic injury. Human ECFCs (hECFCs) were administered by intramuscular injection and hindlimb blood perfusion was measured by laser Doppler analysis at 7-day intervals for 28 days after treatment. Mice were sacrificed after 7 and 28 days and immunohistochemistry for specific human (CD31) and mouse (von Willebrand factor) endothelial antigens was carried out. Before euthanasia, blood samples to assess cytokines and angiogenic growth factor levels were collected. Results: Mice injected with hECFCs showed a prompter and greater recovery of blood flow than controls. Several endothelial cells of human origin were detected at day7 after injection and their number declined progressively. Likewise, a progressive increase of mouse-derived vascular structures were observed, paralleled by the amplified endogenous production of various soluble mediators of angiogenesis, including Vascular Endothelial Growth Factor and Fibroblast Growth Factor. Conclusions: Overall, our findings are consistent with the hypothesis that human ECFCs might expand the endogenous vascular repair potential of recipients and support their possible HLA-independent unconventional use. Graphical abstract: Highlights: Endothelial colony forming cells (ECFCs) are endowed with vascular regenerative ability. ECFC immunogenicity and susceptibility to rejection is unknown. We injected human ECFCs in the ischemic hindlimb of C57BL/6 J mice. Treatment promotes blood flow recovery and endogenous production of angiogenic factors.